Occurrence of Corynebacterium ulcerans and Pasteurella multocida in pet cats and dogs in Klang Valley, Malaysia - Ng, Geok Lim; Abdul Aziz, Saleha; Dhaliwal, Gurmeet Kaur; Bejo, Siti Khairani; Khor, Kuan Hua (Veterinary Association Malaysia, 2020)
Pets especially cats and dogs are known to carry a number of zoonotic pathogens in their mouths, such as Pasteurella multocida and Staphylococcus species while Corynebacterium ulcerans is reported to be emerging in these animals. C. ulcerans produces diphtheria toxin and causes diphtheria-like symptoms in human. This infection is an emerging public health threat in developed countries, with incidence sometimes higher than that of C. diphtheriae. Infection due to P. multocida is often associated with bite wounds and scratches that cause significant morbidity and mortality in humans. Therefore, this study was conducted to determine the occurrence of C. ulcerans and P. multocida in pet cats and dogs in Klang Valley, Malaysia and their antibiotic resistance profiles. Nasal and pharyngeal samples were collected from apparently healthy animals comprising 26 cats and 29 dogs that were presented at four veterinary health care facilities in Klang Valley. The isolates were tested against six antibiotics commonly used in small animal practice. C. ulcerans was not isolated (0%) in this study whereas the occurrence for P. multocida was low (10.9%). P. multocida isolates showed low resistance (16.7% each) to amoxicillin-clavulanic acid, tetracycline, trimethoprim-sulfamethoxazole and cephalexin.